Research process in physical education and sport management - Rokade, P.R. Dr
Physical education plays a part in the lives of almost all children and young people's education around the world. If the physical education experiences of those young people are to be positive and effective, the we need to know something about how it is taught, who is teaching it, what is being taught, and how it can be improved. Research comprises "creative work undertaken on a systematic basis in order to increase the stock of knowledge, including knowledge of humans, culture and society, and the use of this stock knowledge to devise new applications". It is used to establish of confirm facts, reaffirm the results of previous work, solve new or existing problems, support theorems, or develop new theories. A research project may also be an expansion on the past work in the field. Research projects can be used to develop further knowledge on a topic, or in the example of school research project, they can be used to further a student's research prowess to prepare them for future jobs or reports. To test the validity of instruments, procedures, or experiments, research may replicate elements of prior projects or the project as a whole. The present book outlines all the essential aspects of Research Process of Physical Education and Sports. This book is indispensible reading for all students and professionals working in physical education, youth sport, sports coaching and related subjects